2005
DOI: 10.1111/j.0022-202x.2005.23717.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Radiation-Induced Impairment of Tumor Rejection Is Enhanced in Xeroderma Pigmentosum A Gene-Deficient Mice

Abstract: Xeroderma pigmentosum (XP)A gene-deficient mice display dermatologic abnormalities similar to human XP, such as enhanced ultraviolet (UV)-induced acute inflammation and high incidence of UVB-induced skin cancer. We have previously reported that UVB-induced immunosuppression of contact hypersensitivity was greatly enhanced in XPA mice. In the present study, we examined the effects of UVB radiation on tumor rejection in XPA mice. Tumor cells established from UVB-induced squamous cell carcinoma in XPA mice were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…In the former case, initial DNA damage by 7,12dimethylbenz[a]anthracene followed by inflammation by 12-O-tetradecanoylphorbol-13-acetate contributes to the development of cancer, whereas in the latter case, UVB causes the failure of immune surveillance in addition to the initial DNA damage and continual inflammation (Abel et al, 2009;DiGiovanni, 1992;Nishigori et al, 1996). However, the dose causing tumor rejection in Xpa-deficient mice was 0.75 kJ/m 2 , which is much larger than the dose in our study, and it also induced inflammation (Miyauchi-Hashimoto et al, 2005). On the other hand, 7,12-dimethylbenz[a] anthracene induced immune suppression as well as inflammation at the same concentration (Miyauchi-Hashimoto et al, 2001).…”
Section: Discussioncontrasting
confidence: 60%
“…In the former case, initial DNA damage by 7,12dimethylbenz[a]anthracene followed by inflammation by 12-O-tetradecanoylphorbol-13-acetate contributes to the development of cancer, whereas in the latter case, UVB causes the failure of immune surveillance in addition to the initial DNA damage and continual inflammation (Abel et al, 2009;DiGiovanni, 1992;Nishigori et al, 1996). However, the dose causing tumor rejection in Xpa-deficient mice was 0.75 kJ/m 2 , which is much larger than the dose in our study, and it also induced inflammation (Miyauchi-Hashimoto et al, 2005). On the other hand, 7,12-dimethylbenz[a] anthracene induced immune suppression as well as inflammation at the same concentration (Miyauchi-Hashimoto et al, 2001).…”
Section: Discussioncontrasting
confidence: 60%
“…(1) Patients with AD usually have a personal or familial history of other atopic diseases. (2) Population studies have suggested that AD affects 10-20% of all children in most countries at some time during childhood. (3) Moreover, AD is a multifactorial disease, and its pathogenesis and etiology are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…(3) Moreover, AD is a multifactorial disease, and its pathogenesis and etiology are not fully understood. (2) AD is treated using steroids, antihistamines, immunosuppressive agents, and other medications. However, many studies have indicated that long-term use or even abuse of these agents may cause various side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Immunosuppressed contact hypersensitivity (Xpa deficient mice); inhibited intra-tumor migration of NKs and CD8+ T cells (Xpa deficient mice); depressed delayed hypersensitivity in immunized mice; enhanced contact hypersensitivity and skin graft rejection in mice with dermal Langerin+ DCs. [248][249][250][251][252][253][254] Narrowband (NB)-UVB: increased intestinal Tregs, and decreased severity of inflammatory lesions in mouse models of allogeneic GVHD.…”
Section: Uvbmentioning
confidence: 99%